Non-Invasive Treatment in A Case of Post-Ovulatory Egg Stasis in A Burmese Python (Python bivittatus) - Govendan, Puveanthan Nagappan; Kurniawan, Lynn Kaat Laura; Raharjo, Slamet (Indonesia Medicus Veterinus, 2019)
A three-year-old adult female albino gravid Python bivittatus was presented with a complaint of egg retention. It laid one slug egg 48 hours earlier and no oviposition noticed after. The python was very restless and was moving a lot in the enclosure. Physical examination and palpation showed a distended cealomic cavity and radiography performed after confirmed post-ovulatory egg stasis. Fluid therapy, calcium gluconate and hormonal therapy was indicated. Two doses of oxytocin were given by intramuscular injection and oviposition was noticed within 24 hours after second therapy.